Cardiovascular adaptation during action pistol shooting - Fenici, R.; Ruggieri, M. P.; Brisinda, D.; Fenici, P. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: Action Pistol Shooting, implies high degree of physical and psychological stress, however cardiovascular adaptation during competition has not been studied so far. METHODS: We studied six healthy males athletes, during the Italian National Dynamic Pistol Shooting Championship. ECG was monitored and blood pressure (BP) manually measured along the match. RESULTS: Mean heart rate (HR) was close to 100 bpm per minute in all but one shooters. Marked tachycardia, above 180 beats per minute was recorded in four shooters, during "field course" stages. In two cases the heart rate under stress reached about 200 bpm, for the occurrence of paroxysmal atrial arrhythmias. BP behavior was different among the six shooters with mean systolic values ranging between 140 and 170 mmHg and maximal systolic values between 160 e 240 mmHg. CONCLUSIONS: Action Pistol Shooting induces acute elevation of HR and BP, which may reach abnormal values and can be associated with impaired performance and score. Further study is warranted in shooters undergoing combat-like tournaments to evaluate unperceived cardiovascular stress and their coping capability.